Heteroatoms doped metal iron–polyvinylidene fluoride (PVDF) membrane for enhancing oxidation of organic contaminants - Yao, Y.; Lian, C.; Hu, Y.; Zhang, J.; Gao, M.; Zhang, Y.; Wang, Shaobin (Elsevier BV, 2017)
© 2017 Elsevier B.V. Iron nanoparticles (NPs) embedded in S, N-codoped carbon were prepared by one-step pyrolysis of a homogeneous mixture consisting of Fe, S, N, C precursors, and then immobilized in poly (vinylidene fluoride) membranes as a multifunctional catalytic system (NSC-Fe@PVDF) to effectively activate peroxymonosulfate (PMS) and oxidize organic compounds in water. The NSC-Fe@PVDF membranes effectively decolorized organic pollutants at a wide pH range (2.05-10.85), due to the synergistic effects between the S, N-doped carbon and iron NPs. The efficiency depended on the doping types, amount of metal, PMS dosages, reaction temperatures, solution pHs, and organic substrates. In-situ electron spin resonance spectroscopy and sacrificial-reagent incorporated catalysis indicate radical intermediates such as sulfate and hydroxyl radicals are mainly responsible for this persulfate-driven oxidation of organic compounds. Membrane's porous structure and high internal surface area not only minimize the NPs agglomeration, but also allow the facile transport of catalytic reactants to the active surface of metal catalysts. The results demonstrate the morphological and structural features of catalytic membranes enhance the overall catalytic activity.